2015
DOI: 10.1021/acs.biochem.5b00328
|View full text |Cite
|
Sign up to set email alerts
|

The Enzymatic Activity of Lipases Correlates with Polarity-Induced Conformational Changes: A Trp-Induced Quenching Fluorescence Study

Abstract: Triacylglycerol hydrolases (EC 3.1.1.3) are thought to become activated when they encounter the water-lipid interface causing a "lid" region to move and expose the catalytic site. Here, we tested this idea by looking for lid movements in Thermomyces lanuginosus lipase (TL lipase), and in variants with a mutated lid region of esterase (Esterase) and esterase/lipase (Hybrid) character. To measure lid movements, we employed the tryptophan-induced quenching (TrIQ) fluorescence method to measure how effectively a T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(62 citation statements)
references
References 54 publications
6
52
0
Order By: Relevance
“…Bimane-133 shows a marked blue shift (15 nm) and a fluorescence two times higher than the denatured protein at pH 7.3 possibly indicating the probe when reacted to position 133 is located in a confined/hydrophobic environment (Kosower et al, 1982; Skjold-Jørgensen et al, 2015) (Figure 3A and Figure 3—figure supplement 2). To generate quenching pairs, we introduced tryptophan residues on the adjacent subunit β-sandwich (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…Bimane-133 shows a marked blue shift (15 nm) and a fluorescence two times higher than the denatured protein at pH 7.3 possibly indicating the probe when reacted to position 133 is located in a confined/hydrophobic environment (Kosower et al, 1982; Skjold-Jørgensen et al, 2015) (Figure 3A and Figure 3—figure supplement 2). To generate quenching pairs, we introduced tryptophan residues on the adjacent subunit β-sandwich (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…They also suggested the key role that the lid plays in determining the polarity-dependent activation of lipases using a combination of methods measuring enzymatic activity, detecting structural changes using the tryptophan-induced quenching method, and calculating the lid opening energies using an MD simulations, and suggested that mutagenesis of the lid can lower the energy barrier associated with lid opening (Skjold-Jorgensen et al, 2016). Tryptophan-induced quenching fluorescence method has been applied to successfully measure the lid movements in T. lanuginosus lipase and its variants in solvents with different dielectric constants (Skjold-Jorgensen et al, 2015). The results indicated that lid movement is highly dependent on the particular lid residue composition as well as solvent polarity.…”
Section: Engineering the Lid Domains Of Lipasesmentioning
confidence: 99%
“…Further studies have used similar protein engineering strategies in endothelial lipase (EL) , human pancreatic lipase (HPL) , C. rugusa lipase (CRL) , Rhizopus chinensis (RCL) lipase , Aspergillus niger lipase (ANL) . Recently, Skjold‐ Jørgensen et al altered the activation mechanism in Thermomyces lanugiunosus lipase (TLL) by rational design of the lid‐region . All these studies on structurally diverse lipases, suggest that the lid‐region plays a key role in hydrolytic activity, interfacial activation, and substrate specificity.…”
Section: Changing the Activation Mechanism In Tll By Rational Designmentioning
confidence: 99%